2010
DOI: 10.1002/kin.20521
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular potential parameters and combining rules determined from viscosity data

Abstract: The Law of Corresponding States has been demonstrated for a number of pure substances and binary mixtures, and provides evidence that the transport properties viscosity and diffusion can be determined from a molecular shape function, often taken to be a Lennard-Jones 12-6 potential, that requires two scaling parameters: a well depth ε ij and a collision diameter σ ij , both of which depend on the interacting species i and j. We obtain estimates for ε ij and σ ij of interacting species by finding the values tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The parameters specifying this potential for H−O 2 were estimated with conventional combining rules: The well depth ε and length parameter σ for H−O 2 were taken as the geometric and arithmetic means, respectively, of the corresponding parameters for the like systems A″ and 4 A″ PESs was taken. We see that the collision integrals computed with the LJ potential are larger than those from the quantum scattering calculation, except for Ω (2,2) at low temperatures. Moreover, the LJ estimate has a temperature dependence that is much steeper than that of the quantum scattering calculation.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The parameters specifying this potential for H−O 2 were estimated with conventional combining rules: The well depth ε and length parameter σ for H−O 2 were taken as the geometric and arithmetic means, respectively, of the corresponding parameters for the like systems A″ and 4 A″ PESs was taken. We see that the collision integrals computed with the LJ potential are larger than those from the quantum scattering calculation, except for Ω (2,2) at low temperatures. Moreover, the LJ estimate has a temperature dependence that is much steeper than that of the quantum scattering calculation.…”
Section: Discussionmentioning
confidence: 69%
“…These collision integrals are larger for collisions on the 4 A″ PES, reflecting the differences in the magnitudes of the transport cross sections plotted in Figures 3 and 4. The Q n i (2,2) collision integrals for both PESs show a similar dependence upon the rotational level n i and are not plotted here. We see in Figure 5 that the dependence of Q n i (1,1) upon n i is relatively weak at 300 K.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Bastien et al [61] collected recent viscosity data for a number of substances and temperatures and used Powell's method as described by Press et al [62] with a brute force fitting approach to determine ε and ζ. They found a nearly linear -trough‖ in ε, ζ space, such that any parameter pair in the trough yields a viscosity that agrees with experiment within about 1%, as as shown on Figure 2.…”
Section: Pure Speciesmentioning
confidence: 99%
“…15 For unlike systems, the parameters are typically estimated by combination rules. [16][17][18] a) Electronic mail: pjdagdigian@jhu.edu b) Electronic mail: mha@umd.edu Investigations of several systems have shown that the repulsive wall of the LJ 12-6 potential is steeper than predicted by more accurate methods. 1,14 This results in inaccuracies in the prediction of the temperature dependence of the transport properties.…”
Section: Introductionmentioning
confidence: 99%